Association of peripheral arterial disease with all-cause and cardiovascular mortality in hemodialysis patients: a meta-analysis. Issue 1 (December 2016) - Yang, Yi; Ning, Yong; Shang, Weifeng; Luo, Ran; Li, Lixi; Guo, Shuiming; Xu, Gang; He, Xiaofeng; Ge, Shuwang
Abstract Background Recent studies have shown an association between peripheral arterial disease (PAD) and increased risk of mortality in hemodialysis (HD) patients; however, the estimates vary widely and are inconsistent. It is necessary to elucidate the degree of mortality risk for PAD patients in HD population. Methods PubMed, EMBASE, Web of Science and Cochrane Library (from inception to September 4th, 2016) were systematically searched for cohort studies assessing the association between PAD and mortality in HD patients. We calculated the pooled risk ratios (RRs) with 95% confidence intervals (CI) of all-cause and cardiovascular (CV) mortality using random effects models. Subgroup analyses were conducted to explore the source of heterogeneity. Results The search identified 2, 973 potentially eligible records and 10 studies (n = 32, 864) were included. Our meta-analysis revealed that PAD significantly increased the risk of all-cause mortality (RR 2.15, 95 % CI 1.67–2.77, n = 32, 864) and CV mortality (RR 2.99, 95 % CI 1.66-5.38, n = 31, 794) in HD patients after multivariate adjustment. Subgroup analyses showed the study design and follow-up time might be two sources of heterogeneity. Conclusion PAD may be a prognostic marker of all-cause and CV mortality in HD patients. More attention should be paid to diagnosis and management of PAD in HD patients.